المتطلبات اللازمة لعضو الهيئة الادارية في ضوء الحوكمة الجامعية - باشيوة, حسين; قشاو, خولة (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة الى معرفة المتطلبات اللازمة لعضو الهيئة الادارية ( الشخصية والاخلاقية والمهنية والاجتماعية والانسانية ) في ضوء الحوكمة الجامعية، وقد اعتمدت على المنهج الوصفي، لوصف المشكلة وتحليلها وتفسيرها، ومنها تقديم تصور لهذه. وقد توصلت الدراسة الى انه يجب ان لا يتولى منصب عضو الهيئة الادارية الجامعية إلا بعد اجتيازه لعدد من الاختبارات التي تكشف عما لديه من قدرات وإمكانيات تمكنه من النجاح في أداء وظيفته على احسن وجه. وأن يمتلك الكفاءات المهنية، الشخصية، الأخلاقية، الاجتماعية والانسانية التي تمكنه من القيام بدوره على احسن وجه. وأن يمتلك الذهنية الواعية المستنيرة القادرة علي التكيف مع التطورات الحديثة والمستجدة. Abstract: The study aimed to know the necessary requirements for a member of the administrative body (personal, ethical, professional, social and humanitarian), in the light of university governance. The descriptive approach was used, and the study sample consisted of (100) individuals, including (60) males, (40) females. (Personal, professional, social and humanitarian). It includes (skills, behavior, competence, and desired values, and the study concluded that only those who possess professional, personal, ethical, social and humanitarian competencies should take the position of a member of the university administrative body, and possess a conscious, enlightened mind capable of adapting to developments modern and emerging, which enables him to perform his role in the best way.
دراسة تطبيقية
مقال
Keywords: الكفايات(الشخصية والمهنية والاجتماعية والانسانية ; عضو الهيئة الادارية الجامعية ; معايير الجودة الادارية ; مؤسسات التعليم العالي; Competencies (personal, professional, social and humanitarian); Member of the university administrative board; management quality standards; Institutions of higher education